A Rare Axillary Cutaneous Squamous Cell Carcinoma: A Case Report and Literature Review - Carrijo Costa, Pamela; Zafer Merhi, Mahmoud; Amantini Messias, Bruno; Barão da Silva, Diego (International Journal of Clinical Research, 2022)
Background: Non-melanoma skin cancer is the most frequent tumor in Brazil and the world. One of its forms, squamous cell carcinoma (SCC) predominantly affects the old white population in areas of high exposure to the sun. Most SCCs are indolent, evolving with a cure rate higher than 90% within five years. Rarely, metastasis occurs mainly in regional lymph nodes, but it can also happen in the lungs, liver, brain, skin, and bones. There are currently many treatment options; based on the stratification of the neoplasm as high or low risk, an appropriate approach is defined. Case presentation: This report presents the case of a patient with high-risk squamous cell carcinoma affecting an area not exposed to solar radiation and without any other previous triggering factor, which is quite uncommon for this type of tumor. The rarity of the case stems from the lack of scientific reports on the occurrence of SCC in the axillary region, without a history of local chronic inflammatory lesions. The Portuguese, English, and Spanish languages were used to search the database of the main scientific platforms Pubmed, Cochrane Library, Scielo, and Lilacs, with no results similar to the case reported. Conclusion: Despite the fact that the axillary area is not sun-exposed, squamous cell skin cancer manifested as an extensive lesion that required a complex surgical resection with flap repair. Such findings highlight the importance of a thorough physical exam and work-up to diagnose lesions in their early forms which require simple resection procedures and avoid late diagnoses resulting in complex procedures. Such an approach reduces the risk of various complications like wound infection or dehiscence, flap ischemia, or necrosis, among others.